(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article psychologically analyzes the relationship of Grigory Aleksandrovich Pechorin, the main character of Mikhail Lermontov’s novel “Hero of Our Time” with women, and reveals the conflicts between the concepts of “love” and “play” in Pechorin’s character through the characters of Bella, Marie and Vera.